LITERATURE REVIEW: PERSPECTIVES ON RELIGIOUS MODERATION IN MULTICULTURAL SOCIETIES - Sholahuddin Al Ayubi; Iin Inayatul Ummah; Jamadi (ADISAM Publisher, 2024)
This research examines the perspective of religious moderation in a multicultural society and its impact on social harmony. Religious moderation, which emphasises the values of tolerance, mutual respect and interfaith dialogue, is considered an effective approach in dealing with potential conflicts arising from differences in religious beliefs and practices. Through inclusive education, the involvement of moderate religious leaders, and the support of government policies that favour pluralism, religious moderation can be strengthened and implemented more effectively. Despite challenges such as media influence and narrow religious interpretations, cooperation between various stakeholders was identified as a key factor in overcoming these obstacles. The results of this study show that a religious moderation perspective is not only essential in mitigating conflict, but also in building a peaceful and tolerant society amidst cultural and religious diversity.